British Adolescents Are More Likely Than Children to Support Bystanders Who Challenge Exclusion of Immigrant Peers - Gönültaş, Seçil; Ketzitzidou Argyri, Eirini; Yüksel, Ayşe Şule; Palmer, Sally B.; McGuire, Luke; Killen, Melanie; Rutland, Adam (Frontiers in Psychology, 2022)
The present study examined British children’s and adolescents’ individual and perceived group evaluations of a challenger when a member of one’s own group excludes a British national or an immigrant newcomer to the school (Turkish or Australian) from participating in a group activity. Participants included British children (n = 110, Mage in years = 9.69, SD = 1.07, 44 girls, aged 8–11) and adolescents (n = 193, Mage in years = 14.16, SD = 0.92, 104 girls, aged 13–16), who were inducted into their group and heard hypothetical scenarios in which a member of their own group expressed a desire to exclude the newcomer from joining their activity. Subsequently, participants heard that another member of the ingroup challenged the exclusionary act by stating that they should be inclusive. Children’s and adolescents’ individual evaluations of the bystander who challenged the social exclusion of an immigrant peer were more positive than their perceived group evaluations, recognizing that groups are often exclusionary. Only adolescents but not children differed in their individual and perceived group evaluations in the social exclusion of British peers. When the newcomer was an immigrant peer, adolescents were more likely to evaluate the challenger positively in both their individual and perceived group evaluations compared to children. Further, children, compared to adolescents, were more likely to reason about social and group norms to justify their evaluations only when the excluded peer was an immigrant but not when the excluded peer was British. Adolescents were more likely to reason about fairness, rights, and equality. The findings indicate that exclusionary group norms surrounding immigrants begin in childhood. Interventions that focus on changing group norms to be more inclusive could be effective in reducing prejudicial attitudes toward immigrants in childhood.